Examining emotional sequelae of sport concussion - Mainwaring, L. M.; Hutchison, M.; Comper, P.; Richards, D. (Journal of Clinical Sport Psychology, 2012)
Depression, fatigue, irritability, confusion, and general mood disturbance are frequently reported after cerebral concussion in sport. Recent trends in research point to the importance of examining postconcussive emotional disturbances more thoroughly, empirically, and clinically. An overview of the complexity of human emotion and its study is provided herein, followed by a review of emo- tional correlates identified in the existing sparse literature. The significance and clinical implications of identifying emotional correlates of concussion in sport and athletics are discussed.